The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/nu6010124
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Steatohepatitis and Hepatocellular Carcinoma: Implications for Lycopene Intervention

Abstract: Increased prevalence of non-alcoholic fatty liver disease (NAFLD) is one of the consequences of the current obesity epidemic. NAFLD is a major form of chronic liver disease that is highly prevalent in obese and overweight adults and children. Nonalcoholic steatohepatitis (NASH) is the severe form of NAFLD, and uncontrolled inflammation as displayed in NASH has been identified as one of the key events in enhancing hepatic carcinogenesis. Lycopene is a non-provitamin A carotenoid and the pigment principally resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 237 publications
1
39
0
Order By: Relevance
“…Lycopene can accumulate in adipose tissue (10) and modulate adipose lipid/inflammationassociated signaling cascades (41,42). Evidence showed that the portal vein directly connects the liver with the visceral MAT (43,44), and visceral fat content is highly correlated with the degree of liver steatosis in humans (45,46).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lycopene can accumulate in adipose tissue (10) and modulate adipose lipid/inflammationassociated signaling cascades (41,42). Evidence showed that the portal vein directly connects the liver with the visceral MAT (43,44), and visceral fat content is highly correlated with the degree of liver steatosis in humans (45,46).…”
Section: Discussionmentioning
confidence: 98%
“…In vivo and in vitro studies have suggested that lycopene may use multifaceted mechanisms to reduce CVD and NAFLD risks (8)(9)(10), mechanisms that include modulating cholesterol metabolism, serving as an antioxidant, and inhibiting inflammation (8)(9)(10). Of note, NAFLD patients have substantially reduced plasma lycopene concentration (11), suggesting potential interactions between low lycopene status and CVD risk.…”
Section: Introductionmentioning
confidence: 95%
“…Table 1 reports a brief description of some foods characterizing Sicilian countryside dietary habits [27,28,29,30,31,32]. As previously stated, olive oil plays a central role in MedDiet [2,11,33,34,35] and a glass of wine with meals may be assumed every day [2,11].…”
Section: Mediterranean Diet Nutrients Phytochemicals and Hormesismentioning
confidence: 99%
“…Lycopene has been shown to activate the Nrf2/ HO-1 pathway and can protect against nephrotoxicity induced by gentamicin, adriamycin, and cisplatin (28,31,(36)(37)(38)(39). Lycopene displays antioxidant and anti-inflammatory effects; in one clinical trial, the data suggested that it may play an important role in protection against various chronic diseases (e.g., cancer) (40). In the present study, we investigated the nephroprotective effect of lycopene on polymyxin-induced nephrotoxicity and the involvement of the Nrf2/HO-1 pathway in a mouse model.…”
mentioning
confidence: 98%